2023
DOI: 10.3389/fpsyg.2023.1104897
|View full text |Cite
|
Sign up to set email alerts
|

Research on the relationship between physical activity, sleep quality, psychological resilience, and social adaptation among Chinese college students: A cross-sectional study

Abstract: BackgroundSleep quality has become a frequent and prominent public health problem in Chinese universities, which seriously hinders the healthy development of college students and the improvement of the quality of higher education.ObjectiveThe purpose of this study is to explore the relationship between physical activity and sleep quality among Chinese college students, and the mechanism of psychological resilience and social adaptation, and provide suggestions for improving the sleep quality among Chinese coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Individuals with higher levels of cell phone addiction may quickly recognize negative emotions, such as anxiety and loneliness, and have lower levels of psychological resilience. Conversely those with high psychological resilience do not routinely contemplate all potential stress-related implications in their daily lives, thereby experiencing better sleep compared to their counterparts with lower levels of psychological resilience ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher levels of cell phone addiction may quickly recognize negative emotions, such as anxiety and loneliness, and have lower levels of psychological resilience. Conversely those with high psychological resilience do not routinely contemplate all potential stress-related implications in their daily lives, thereby experiencing better sleep compared to their counterparts with lower levels of psychological resilience ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Belinda Hernández et al, poor sleep quality and physical activity are associated with a higher risk of chronic diseases, including hypertension(36). Yongbin Li et al showed a signi cant correlation between physical activity and sleep (37). Merellano-Navarro et al found that being a man and having appropriate physical activity improves sleep quality regardless of age (38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sophomores had already adapted to the learning environment and may have found it easier to adapt to the internet than freshmen. Over time, the changes in students' study methods and thinking ability gradually strengthens their study ability (Li & Gu, 2011).…”
Section: Discussionmentioning
confidence: 99%